Analysis Technology Acceptance Model (TAM) Pre-Service Elementary School Teachers - Dina, Lia Nur Atiqoh Bela; Faizah, Silviana Nur; Anggraini, Ade Eka (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This study seeks to reveal the level of technology acceptance of pre-service elementary school teachers, and the model of technology acceptance of pre-service elementary school teachers and analyze the relationship between the two components of pre-service elementary school teachers' TAM (perceived usefulness and perceived ease of use). This research, in its implementation, uses quantitative research methods with explanatory, descriptive research types. Data collection was carried out through an online survey. The population in this study were all students in the Madrasah Ibtidaiyah Teacher Education study program at the Islamic University of Malang and the Islamic University of Lamongan. While the sample in this study were 100 pre-service elementary school teachers (students who had already implemented PPL) in the Madrasah Ibtidaiyah Teacher Education study program, the Islamic University of Malang and the Islamic University of Lamongan, which were taken using a proportional random sample technique. The instrument used was a questionnaire containing two variables: perceived usefulness and perceived ease of use. Statistical analysis of the Structural Equation Model (SEM) was used as a data analysis method. The study results showed that the level of technology acceptance for pre-service elementary school teachers was in the high category. The goodness of fit for the chi-square table was 94.842 < 98.27018, CMIN/DF 1.232 with a probability of 0.082, RMSEA 0.048, GFI 0.905, TLI 0.986, and CFI 0.991. The size of the feasibility model is included in the "good/appropriate" category. Furthermore, the results of the analysis show that perceived usefulness (PU) has a positive and significant relationship with perceived ease of use (PEOU).